AB1199-HPR Improving triage to appropriate treatment level by using a combination of screening tools in patients at risk of developing chronic back pain. (15th June 2017) - Haglund, E; Olsson, C; Bremander, A; Bergman, S
Abstract : Background: The screening instrument STarT (Subgroups for Targeted Treatment) Back Screening Tool (SBST) identify patients at risk of developing chronic back pain in order to facilitate triage to appropriate treatment level. The SBST takes into account known risk factors such as activity limitations, kinesiophobia and psychological health. However, SBST does not consider pain distribution which is a known predictor of chronic widespread pain (CWP). According to evidenced clinical practice patients with CWP should be referred to multimodal rehabilitation (1). Objectives: The purpose of the study was to compare screening by SBST with screening of multisite chronic widespread pain (MS-CWP) in a group of patients with back pain and to analyze to what extent the two screening methods identify the same patients at higher risk. Methods: 73 individuals with a report of chronic back pain (≥3 months during last year) age 40–70 years responded to both screening tools. The SBST stratify patients into low, medium or high risk groups. A pain mannequin was used to categorize patients into no chronic pain (NCP), chronic regional pain (CRP) or chronic widespread pain (CWP) and number of painful areas (0–18). A presence of a CWP in combination with ≥7 painful areas was stratified as MS-CWP. The outcome of the different screening tools was analyzed by cross tabulations. The Roland-Morris Disability Questionnaire (RMDQ, 0–24), health related quality of life (EQ5D, 0–1), Fear-Avoidance Beliefs Questionnaire about physical activity (FABQ-PA, 0–24) and work (FABQ-Work, 0–42), Hospital Anxiety (HAD-A, 0–21) and Depression scale (HAD-D, 0–21) were used to describe physical function, health related quality of life, kinesiophobia and mental health. Results: The mean (SD) age was 59 (8) years, 63% were women. Self-reports of physical function (RMDQ) were 4.5 (4.8), health related quality of life (EQ5D) 0.71 (0.21), kinesiophobia (FABQ-PA and FABQ-Work) 8.3 (5.9) and 14.7 (11.1), and mental health (HAD-A and HAD-B) 8.8 (2.0) and 4.5 (1.7). Comparing the different screening methods, 5 patients (7%) were at high risk as captured by SBST while using the pain mannequin 38 (52%) patients had CWP and 22 (30%) had MS-CWP. No patients in the SBST high risk group had NCP, but 31 (50%) in the SBST low risk group reported CWP, and 16 (26%) reported MS-CWP. In the medium risk group 3 reported CWP, and 3 were also categorized as MS-CWP. Conclusions: SBST and the pain mannequin as screening tools partly capture different patients at high risk of developing chronic back pain. Using a combination of the two instruments may improve the ability to facilitate triage to appropriate treatment level. References: Macfarlane GJ et al. EULAR revised recommendations for the management of fibromyalgia. Ann Rheum Dis. 2017;76(2):318–328. Disclosure of Interest: None declared